Wind Loads of Solar Water Heaters: Wind Incidence Effect. (27th October 2014) - Chou, Chin-Cheng; Chung, Kung-Ming; Chang, Keh-Chin
Abstract : For applications of solar thermal energy, solar water heaters (SWHs) are becoming common. In this study, the effect of a crosswind on the aerodynamic characteristics of residential (an inclined flat plate with a horizontal cylinder) and large-scale SWHs (an inclined flat plate only) is experimentally investigated. The tests are conducted in a low speed wind tunnel and the relative wind direction with respect to the test model, β, ranges from 0 to 135 deg. Measurements of the mean and fluctuating pressures are presented. These results demonstrate that higher suction and fluctuating pressure are observed near the upwind corner, particularly for the test case ofβ = 30 deg.